2018
DOI: 10.3389/fpls.2017.02226
|View full text |Cite|
|
Sign up to set email alerts
|

miR156/SPL10 Modulates Lateral Root Development, Branching and Leaf Morphology in Arabidopsis by Silencing AGAMOUS-LIKE 79

Abstract: The developmental functions of miR156-SPL regulatory network have been extensively studied in Arabidopsis, but the downstream genes regulated by each SPL have not been well characterized. In this study, Next Generation Sequencing-based transcriptome analysis was performed on roots of wild type (WT) and miR156 overexpression (miR156OE) plants. One of the SPL genes, SPL10, which represses lateral root growth in Arabidopsis, was significantly downregulated in miR156OE plants. A transcription factor, AGAMOUS-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 59 publications
3
82
0
Order By: Relevance
“…Tansley review New Phytologist initiation sites (Moreno-Risueno et al, 2010). By contrast, knockout lines of AGL79 have more LRs in than wild-type plants do (Gao et al, 2018). Table S1 summarizes the available expression data for several MADS-box genes mentioned in this review in different plant species.…”
Section: Reviewmentioning
confidence: 99%
“…Tansley review New Phytologist initiation sites (Moreno-Risueno et al, 2010). By contrast, knockout lines of AGL79 have more LRs in than wild-type plants do (Gao et al, 2018). Table S1 summarizes the available expression data for several MADS-box genes mentioned in this review in different plant species.…”
Section: Reviewmentioning
confidence: 99%
“…Here, we showed that overexpression of SPL10 promotes expression of FUL , LFY , AP1 , SOC1 and miR172b , and SPL10 binds directly to the promoters of FUL and AP1 . AGL79 , a MADS‐box protein‐encoding gene, was also found to be a direct target gene of SPL10 (Gao et al ., ; Fig. ).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, HISTONE ACETYLTRANSFERASE 1 (HAC1), an evolutionarily conserved coactivator, has been reported to physically and functionally associate with MED25 to activate the expression of jasmonic acid responsive genes by H3K9 acetylation (An et al ., ). SPL10 also enhances the transcript levels of miR172b , AGL79, FUL , and AP1 during floral transition and shoot maturation (Shikata et al ., ; Wu et al ., ; Gao et al ., ; Fig. ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations